Sub-angstrom strain in high-entropy intermetallic boosts the oxygen reduction reaction in fuel cell cathodes - Xueru Zhao; Hao Cheng; Lijun Wu; Qi Zhang; Xiaobo Chen; Nebojsa Marinkovic; Chenzhao Li; Sha Tan; Enyuan Hu; Lu Ma; Yimei Zhu; Jian Xie; et al. (Nature Communications)
Abstract The strain effect of high-entropy intermetallic (HEI) catalysts on oxygen reduction reaction (ORR) performance remains largely unexplored, primarily due to the significant challenges associated with characterizing and calculating the intricate local coordination environments. Here, we design a nitrogen (N)-doped L10-ordered PtCoNiFeCu intermetallic catalyst supported on Ketjenblack carbon (N-HEI/KB), and reveal the origin of the sub-angstrom strain in N-HEI and its impact on ORR performance by combining atomic-scale characterization and theoretical calculations. The synergistic interplay of the sub-angstrom strain, the pinning effect of metal-N bonds, and the high-entropy effect contribute to the competitive stability of N-HEI/KB catalysts, providing high current density of 1388 mA cm-2 at 0.7 V after 90,000 cycles even under harsh heavy-duty vehicle conditions. These findings broaden the avenues for designing high-performance high-entropy intermetallic cathode electrocatalysts.